2007
DOI: 10.1038/sj.gene.6364446
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and evolutionary origins of autoimmune susceptibility alleles in natural mouse populations

Abstract: The evolutionary origin of genetic diversity in the SLAM/CD2 gene cluster, implicated in autoimmune lupus susceptibility in mice, was investigated by sequence analysis of exons from six members of the cluster in 48 wild mouse samples derived from the global mouse population. A total of 80 coding region SNPs were identified among the six genes analyzed, indicating that this gene cluster is highly polymorphic in natural mouse populations. Phylogenetic analyses of these allelic sequences revealed clustering of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…Given previous reports implicating Slam genes in NKT development (33, 34), as well as reports demonstrating numerous polymorphisms at Slam family loci (36, 37), we evaluated the differential expression of members of this gene family on macrophages and NKT cells between the parental C57BL/6J and B6.129c1 congenic mice. We used a panel of mAbs to compare the expression of SLAMF1 (CD150), SLAMF2 (CD48), SLAMF3 (CD229), SLAMF5 (CD84), and SLAMF6 (Ly108) between C57BL/6J and B6.129c1 CD11b + Gr1 hi and CD11b + Gr1 lo monocyte/macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given previous reports implicating Slam genes in NKT development (33, 34), as well as reports demonstrating numerous polymorphisms at Slam family loci (36, 37), we evaluated the differential expression of members of this gene family on macrophages and NKT cells between the parental C57BL/6J and B6.129c1 congenic mice. We used a panel of mAbs to compare the expression of SLAMF1 (CD150), SLAMF2 (CD48), SLAMF3 (CD229), SLAMF5 (CD84), and SLAMF6 (Ly108) between C57BL/6J and B6.129c1 CD11b + Gr1 hi and CD11b + Gr1 lo monocyte/macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with reports demonstrating that targeted deletion of members of the signaling lymphocytic activation molecule (SLAM) receptor family (34), as well as the intracellular signaling molecule SLAM-associated protein (SAP) (35), results in impaired NKT cell development. Interestingly, extensive polymorphism at the Slam locus distinguishes two major Slam haplotypes in commonly used inbred strains of mice (36, 37). Whereas Slam haplotype-2 is present in NOD, 129X1/SvJ, 129S1/SvImJ, BALB/cJ, and SM/J, Slam haplotype -1 is present in C57BL/6, C57BR/cdJ, and C57L/J among others (36).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, other polymorphic genes within the sst1 region may also contribute to the observed differences between the sst1 susceptible and sst1 resistant animals. Indeed, clustering of functionally related genes in mammalian genomes, as well as multiple functional polymorphisms within candidate chromosomal loci, has been documented in other forward genetic analyses of inflammatory diseases [53].…”
Section: Discussionmentioning
confidence: 99%
“…Homozygosity disequilibrium in the MHC region, which has been shown to contain the important functional genes related to RA and other autoimmune diseases [64], [65], [73],[74], results in a loss of genetic diversities and thereby influences quantitative and/or qualitative alternations of expression profiles. Some studies have found that autoimmunity susceptibility genes are positively selected in RA [75], [76], [77], [78]. Selected alleles accumulate in the gene pool over time and consequently increase the probability of generating an ROH.…”
Section: Discussionmentioning
confidence: 99%